2016
DOI: 10.4238/gmr.15017398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polymorphisms and transcriptional activity of the proto-oncogene KIT located on both autosomal and B chromosomes of the Chinese raccoon dog

Abstract: ABSTRACT. B chromosomes are dispensable and co-exist with autosomal and sex chromosomes. The karyotype of the Chinese raccoon dog (Nyctereutes procyonoides procyonoides) comprises 0-4 B chromosomes. The proto-oncogene KIT is found on all B chromosomes of the Chinese raccoon dog. In the present study, partial DNA and mRNA sequences of KIT were amplified and sequenced from four individuals containing B chromosomes. Sequence analyses revealed that polymorphisms including single nucleotide polymorphisms (SNPs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Nucleolus organiser region (NOR)-like and telomeric sequences were also reported in B chromosomes of the Chinese raccoon dog [Wurster-Hill et al, 1988;Szczerbal and Switonski, 2003]. However, the finding of coding DNA sequences in canid B chromosomes, identified as duplicated genes shared with A chromosomes, changed the previous view [Graphodatsky et al, 2005;Yudkin et al, 2007;Duke Becker et al, 2011;Li et al, 2016].…”
contrasting
confidence: 42%
“…Nucleolus organiser region (NOR)-like and telomeric sequences were also reported in B chromosomes of the Chinese raccoon dog [Wurster-Hill et al, 1988;Szczerbal and Switonski, 2003]. However, the finding of coding DNA sequences in canid B chromosomes, identified as duplicated genes shared with A chromosomes, changed the previous view [Graphodatsky et al, 2005;Yudkin et al, 2007;Duke Becker et al, 2011;Li et al, 2016].…”
contrasting
confidence: 42%
“…Protooncogene KIT was discovered in both NPP and NPV Bs [ 18 ]. In NPP, B chromosomal copies of KIT were found to be enriched with sequence variants, but not transcribed [ 63 ]. Using PCR mapping it was shown that the KIT region in NPP Bs also includes the 5′ part of neighboring KDR gene [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two other enzymes, DOPAchrome tautomerase ( DCT ) and tyrosinase-related protein 1 ( TYRP1 ), influence the nature of the intermediates and properties of the eumelanins20. Research on KIT 31 in raccoon dog reveals that the B Chinese raccoon dog version of KIT lacks transcriptional activity. We surmised that the expression of KIT is not an influencing factor in the B mutation from the W. Moreover, our transcriptome results showed that the expression of the TYR, TYRP1 and MC1R genes was significantly down-regulated in B, which was verified via qRT-PCR, although MITF was not down-regulated.…”
Section: Discussionmentioning
confidence: 99%